2000
DOI: 10.1590/s0103-50532000000300018
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behavior of rhodium acetamidate immobilized on a carbon paste electrode: a hydrazine sensor

Abstract: O comportamento eletroquímico do acetamidato de ródio imobilizado em pasta de carbono e as potencialidades para construção de sensores foram avaliados. O complexo imobilizado mostrou boa estabilidade e propriedades redox, sendo observados dois pares redox reversíveis com potenciais médios entre 0,15 e 0,55 V vs SCE. Entretanto, a resolução dos picos voltamétricos mostrou-se dependente do eletrólito suporte. A correlação entre a capacidade coordenante do eletrólito e seus respectivos potenciais médios sugere qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…In Table 3, some of the electroanalytical parameters obtained in this research are compared with those previously reported by others. [1][2][3][4]7,9,12,[14][15][16][17][18][47][48][49][50][51][52][53][54][55] A comparison of the analytical parameters of hydrazine determination at various modified electrode surfaces shows that the proposed modified electrode has advantages such as wide linear dynamic range (4.0-750.4 mM) and good detection limit (1.1 mM) for hydrazine determination.…”
Section: Chronoamperometric and Amperometric Studies Of Electrocataly...mentioning
confidence: 99%
“…In Table 3, some of the electroanalytical parameters obtained in this research are compared with those previously reported by others. [1][2][3][4]7,9,12,[14][15][16][17][18][47][48][49][50][51][52][53][54][55] A comparison of the analytical parameters of hydrazine determination at various modified electrode surfaces shows that the proposed modified electrode has advantages such as wide linear dynamic range (4.0-750.4 mM) and good detection limit (1.1 mM) for hydrazine determination.…”
Section: Chronoamperometric and Amperometric Studies Of Electrocataly...mentioning
confidence: 99%
“…Some Schiff base complexes were also used for similar purposes. 817,818 Finally, other organometallic electrocatalysts have been reported as CPE modifiers, such as rhodium acetamide, 819 iron(II)-nitroprusside, 820 or Co(II)-1-alkyl-1H-benzo [d] 1-3 triazole derivatives 821 for sensing of some pollutants.…”
Section: Organometallic Complexesmentioning
confidence: 99%
“…Studies made in solutions having different pH showed that the intensity of the current peak densities was sensitive to the pH change as illustrated in Figure 5 with the efficiency increasing at higher pH values. This behavior is attributed to the lower affinity of the protonated hydrazine at low solution pH for the metallic center of the porphyrin [38,39].…”
Section: Electrocatalytic Oxidation Of the Hydrazinementioning
confidence: 99%